Pharmacokinetic Analysis of the Bioavailability of AQUATURM®, a Water-Soluble Curcumin Formulation, in Comparison to a Conventional Curcumin Tablet, in Human Subjects - Jabur, Lillian; Pandey, Rishi; Mikhael, Meena; Niedermayer, Garry; Gyengesi, Erika; Mahns, David; Münch, Gerald (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: Curcumin, the principal bioactive component of Curcuma longa, is known for its anti-inflammatory, antioxidant, and neuroprotective properties. Despite its therapeutic potential, curcumin exhibits poor oral bioavailability due to low solubility, rapid metabolism, and limited gastrointestinal absorption. Various delivery systems have been developed to overcome these limitations. This study aimed to evaluate and compare the pharmacokinetic profile of AQUATURM®, a novel, water-soluble curcumin formulation, with that of a widely available commercial curcumin supplement. Methods: A randomized, double-blind, two-period crossover study was conducted in 12 healthy adult participants (6 male, 6 female; aged 20–45 years). Each participant received a single oral dose of either AQUATURM® or the comparator product, followed by a 7-day washout period before receiving the alternate treatment. Blood samples were collected at multiple time points over a 12-h period post-dosing. Plasma curcumin concentrations were quantified using ultra-performance liquid chromatography with tandem mass spectrometry (UPLC-MS/MS). Results: AQUATURM® achieved a significantly higher systemic exposure compared to the comparator, with a more than 7-fold increase in area under the curve (AUC0–12h) and higher peak plasma concentrations (Cmax). AQUATURM® also maintained detectable curcumin levels for the full 12-h observation period, whereas levels from the comparator fell below quantification limits in most participants after 4 h. Conclusions: AQUATURM® significantly enhances curcumin bioavailability in humans compared to a standard curcumin formulation. These pharmacokinetic improvements support its potential for greater clinical efficacy and warrant further evaluation in therapeutic setting